2005
DOI: 10.2475/ajs.305.5.369
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric growth of the Pyrenees revealed through measurement and modeling of orogenic fluxes

Abstract: ABSTRACT. Orogenic asymmetry is ubiquitous in terms of topography, structure and metamorphism, but the relative influences of climate and tectonics in determining such asymmetry remain contentious. This study demonstrates that for the case of the European Pyrenees, orogenic asymmetry is not defined by inherited structural asymmetry, nor by orographic asymmetry of precipitation, but is the simple consequence of the inherent tectonic growth of a doubly-vergent orogen.The Discrete element model experiments are us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
276
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(296 citation statements)
references
References 81 publications
20
276
0
Order By: Relevance
“…These cycles last on the order of 15 -200,000 model years. Our models, along with other numerical [Naylor and Sinclair, 2007] and analog models [Hoth et al, 2006; and some well dated examples from active orogens [Masaferro et al, 2002;Hubert-Ferrari et al, 2005;Sinclair et al, 2005], suggest that transient accommodation of strain may be common. Thus, caution should be applied when extrapolating long-term slip rates from varying temporal scales.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…These cycles last on the order of 15 -200,000 model years. Our models, along with other numerical [Naylor and Sinclair, 2007] and analog models [Hoth et al, 2006; and some well dated examples from active orogens [Masaferro et al, 2002;Hubert-Ferrari et al, 2005;Sinclair et al, 2005], suggest that transient accommodation of strain may be common. Thus, caution should be applied when extrapolating long-term slip rates from varying temporal scales.…”
Section: Discussionmentioning
confidence: 54%
“…Masaferro et al [2002] showed that the Neogene-Quaternary growth of the Santaren anticline (Cuban fold and thrust belt) is characterized by several tectonic uplift pulses of different duration and intensity, interrupted by periods of variable duration in which no fold growth occurred. The Pyrenees show a punctuated pattern of exhumation [Sinclair et al, 2005]. Given these examples and results from both numerical [Naylor and Sinclair, 2007; this study] and analog [Hoth et al, 2006[Hoth et al, , 2007 modeling, it appears that transient accommodation of strain may be a rather common process.…”
Section: Thrust Cycling Within the Models And Naturementioning
confidence: 72%
“…16), which produced major crustal thickening, surface uplift and expansive molasse sedimentation in both foreland basins (Beaumont et al, 2000;VergĂ©s et al, 2002;Biteau et al, 2006;Teixell et al, 2016). In parallel, rapid exhumation-related cooling, recorded by thermochronology, took place in the Axial Zone, and continued until the Miocene (Fitzgerald et al, 1999;Sinclair et al, 2005;Jolivet et al, 2007;Metcalf et al, 2009;Bosch et al 2016;Labaume et al, 2016a,b). Teixell et al (2016) propose that by late-mid to late Eocene times the stretched and pulled-apart tracts of lower crust (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…The doubly vergent asymmetric structure characterizes a ~150-km-wide surface expression of the Hercynian basement, thin-skinned fold-thrust belts shown by the 250-km-long deep seismic survey (ECORS Pyrenees profile; Choukfoune 1989) from the Aquitaine basin to the Ebro basin of the Pyrenees (Sinclair et al 2005). This structure is considered to have formed in the Pyrenees as a result of northward subduction of the Iberian plate beneath the East European craton during Late Cretaceous to early Miocene times (Roest and Srivastava 1991;Sinclair et al 2005).…”
Section: Tectonic Implication Of the Low-angle Southward-dipping Thrustmentioning
confidence: 99%